ASSESSMENT OF THE ENERGY CONSUMPTION OF FRICTION COUPLES OF DISC-PAD BRAKE DEVICES - Volchenko, Dmytro; Zhuravlоv Dmytro; Voznyi, Andrii; Prysyazhny, Andriy; Nishchuk, Viktor (Problems of Friction and Wear, 2026)
The materials of the article have conducted studies of energy loading in relation to vehicle disc brakes, which allowed us to establish the following: specific heat losses in the disc friction zone change in time according to the law of simple harmonic oscillation with the same oscillation period as the ambient temperature oscillation period, but with a phase shift; it has been confirmed by calculation that the thin surface layer of the disc friction zone is subjected to cyclic thermal loading of an impulse and long-term nature during vehicle braking modes, after which thermal waves penetrate deep into the thickness of the brake disc; the main parameter of the energy loading of friction pairs is the local temperature gradient in the zone of local frictional interaction of their microprotrusion contact spots, which significantly affects the operational parameters of the brake with its fluctuation properties; the local potential acts as a function of the fluctuating temperature and the established temperature of the brake friction pairs.